O homem, uma mulher: um estudo psicanalítico sobre as fórmulas da sexuação - Silveira, Aline Emílio da Mota (2019)
"What is a man? What is a woman?” These questions are highlighted today and have been the subject of studies under different theoretical conceptions. Some questions follow a naturalistic logic emphasizing on biological aspects. In opposition, there are studies focusing on the culture field. This study is built under the Lacan’s theories, considering the importance of psychoanalytical perspective for discussions about man and woman in the contemporary world. Lacan states that the unconscious operation is not biological, even though Freud, in his work, has addressed sex relationships in many ways. In his teaching, Lacan proposes the sexuation formulas, a Lacanian tool to situate the relationship of each subject with his pleasure. The author develops four formulas that are presented in a table composed of four spaces separated by a bar. In this table, the left side refers to the man side, and the right side refers to the woman side. In the face of that, the guiding research question arises, “Does the fact that Lacan proposes two distinct sides involve a binary proposition?” To answer this question, a theoretical research was carried out in psychoanalysis emphasizing on the Lacan’s seminar 20, entitled Encore, moment in which the author presents the sexuation formulas. In addition to the aforementioned seminar, contemporary authors who study this matter and other psychoanalytic works have also been taken into account. This research led to the conclusion that a quick reading would result in a binary interpretation of the formulas proposed. By this study, some ways could be noticed in which 'man' and 'woman' manifest themselves in relation to looks, differences, fluidity, and attempts to overcome the sexual relationship that does not exist. However, it was found by this research that the sexuation formulas are related to the submission of the speaking being to the phallic function, which will reflect on the ways of pleasure, on the knowledge, and on the loving partnerships. Faced with the aphorism that there is no sexualrelationship, it is up to each individual to create singular solutions for a non-relationship. That is, more than a pair-binary logic, the formulation supports the "one by one"/"case by case." This talks about the contingency character of each speaker's relationship with his pleasure, pointing out that this is not about an evidence and that there are no guarantees.